Optimization of the training method for the turns of young gymnasts, taking into account the level of development of the ability to maintain balance - Alfiia Deineko; Olha Riabchenko (Kharkiv State Academy of Physical Culture, 2019)
Purpose: substantiate the effectiveness of using the methodology for developing the ability to maintain balance, which affects the technique of turns 13-15 years old athletes in rhythmic gymnastics. Material & Methods: study involved 13-15 years old athletes, engaged in rhythmic gymnastics. The control group consisted of 10 gymnasts and the experimental group of 10 gymnasts. To solve the tasks, the following research methods were used: theoretical analysis and generalization of literary sources; pedagogical observations; pedagogical testing of the level of development of the ability to maintain balance; expert assessment method; pedagogical experiment; methods of mathematical statistics. Results: the author's method of developing the ability to maintain balance by young gymnasts was developed. The positive influence of using means of developing the ability to maintain balance on the technique of turns by athletes 13-15 years old in rhythmic gymnastics was revealed. Conclusion: an analysis of the results of the study shows that increasing the level of development of the ability to maintain balance by athletes 13-15 years old directly affects the improvement of the technique for turns competitive programs in rhythmic gymnastics.